Vivienda colectiva y productiva en El Barrio La Ciudadela Siglo XXI (2023)
In the XXI century citadel of the municipality of Florencia-Caquetá, due to the exponential growth of the area, the formation of unplanned urban settlements and the growth trend in that expansion area have resulted in the phenomenon of urban voids, which as the name implies, are spaces that have not been developed or implemented an urban treatment, which disarticulates the already established urban structure. That said, this research aims to analyze the trends and dynamics of formation of informal settlements and how these can be efficiently articulated with urban voids. Taking into account the research, it is planned to generate a treatment of urban development as proposed that articulates the full and empty of the current urban structure, considering that these undeveloped spaces can become very interesting elements of integration in the conformation of informal settlements and improvement of the spatial segregation of the municipality.